Comparison of dose-adjusted EPOCH-R and R-CHOP in diffuse large B-cell lymphoma with high Ki67 expression: Results from a prospective observational study - Wenxin Jiang; Peng Liu (PLoS ONE, 2026)
Objectives To compare the safety and efficacy of first-line dose-adjusted EPOCH-R (DA-EPOCH-R) versus R-CHOP treatment in diffuse large B-cell lymphoma (DLBCL) patients with high Ki67 expression. Methods A retrospective analysis of DLBCL patients receiving R-CHOP determined the threshold of high Ki67 expression predicting 2-year progression-free survival (PFS) events using receiver operating characteristic (ROC) curve. Then we initiated a prospective, observational study evaluating DA-EPOCH-R therapy for DLBCL with high Ki67 expression, and selected a retrospective R-CHOP cohort to perform a propensity score-matched (PSM) analysis. Primary endpoints were PFS and overall survival (OS). Results A Ki67 threshold of 82.5% was determined using ROC in the retrospective analysis of 376 DLBCL cases, thus the threshold was ultimately set at 80%. A total of 29 patients receiving DA-EPOCH-R were enrolled in the prospective study, the enrollment was terminated due to the conditional power and a slow accrual. Following 1:1 PSM, no PFS (HR 0.93, 95% CI: 0.47–1.84, p = 0.83) and OS (HR 1.28, 95% CI: 0.42–3.83, p = 0.66) benefit of DA-EPOCH-R versus R-CHOP was observed, with a nearly significantly higher frequency of grade ≥ 3 hematological adverse events (AEs) observed in the DA-EPOCH-R group (p = 0.052). Notably, only 37.9% (11/29) of patients executed dose escalation, which indicated a worse tolerance to this intensified regimen of the East Asians. Conclusions No significant survival benefit from DA-EPOCH-R treatment was observed for DLBCL with high Ki67 expression, which may be attributed to the poorer tolerance in the East Asian population.